Reimagining Access to Justice in the Poor People’s Courts - MacDowell, Elizabeth L. (2015)
Access to justice efforts have been focused more on access than justice, due in part to the framing of access to justice issues around the presence or absence of lawyers. This article argues that access to justice scholars and activists should also think about social justice and provides a roadmap for running a legal services program geared toward making court systems more just. The article also further develops the concept of “poor people’s courts,” a term that has been used to describe courts serving large numbers of low-income people without representation. The article argues that access to justice efforts can and should prioritize responses that address the unique, subordinating impacts of these courts, including those relating to race, class and gender bias, state intervention, and the punitive effects of intersecting state systems. In this context, the article proposes a new theory of access to justice as a counter-hegemonic practice; one that is aimed at challenging dominant ideologies and transforming subordinating systems, as well as delivering legal services